EVALUATION OF COMPETENCY-BASED CAREER DEVELOPMENT AND TRAINING PROGRAMMES IN IMPROVING EMPLOYEE PERFORMANCE: A THEORETICAL AND PRACTICAL STUDY IN MANUFACTURING COMPANIES - Eloh Bahiroh; Sri Ndaru Arthawati (Adisam Publisher, 2025)
This study aims to analyse, both theoretically and practically, the effectiveness of career development programmes and competency-based training in encouraging improved employee performance in a manufacturing company environment. The method used is a literature review that refers to various scientific literature, research journals, and empirical reports relevant to the field of human resource management. The results of the study show that planned career development and competency-oriented training can increase employee motivation, productivity, and loyalty. Theoretically, the integration of competency theory, motivation theory, and career development theory explains how the formation of individual competencies directly affects organisational performance. Meanwhile, in practical terms, the implementation of competency-based programmes in manufacturing companies has been proven to increase work efficiency, reduce operational error rates, and strengthen the workforce's readiness to face industrial transformation. This study emphasises the importance of continuous evaluation of training and career development programmes as part of a strategy for developing superior and highly competitive human resources.